Construction of amphiphilic networks in blend membranes for CO2 separation - Wang, Jiangnan; Lv, Xia; Huang, Lu; Li, Long; Li, Xueqin; Zhang, Jinli (The Korean journal of chemical engineering, 2023)
Blend membranes have attracted great attention because they can combine the advantages of different polymers. To investigate the effect of amphiphilic polymer on the separation performance of blend membranes, a series of blend membranes were designed and fabricated by blending an amphiphilic polymer of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) into poly(ether-block-amide) (Pebax) polymer for CO 2 separation. For the as-prepared Pebax/PEDOT:PSS blend membranes, the interconnected CO 2 -philic networks were constructed by hydrophilic anionic chains of PSS − for accelerating CO 2 transport. Meanwhile, non-CO 2 -philic networks were constructed by the hydrophobic cationic chains of PEDOT + , which distributed around the PSS − chains to provide low friction diffusion for CO 2 . Therefore, the amphiphilic polymer of PEDOT:PSS was an excellent material for improving CO 2 separation performance of blend membranes. The results showed that the Pebax/PEDOT:PSS blend membranes were endowed with excellent CO 2 separation performance. Pebax/PEDOT:PSS blend membrane demonstrated the optimal separation performance with a CO 2 permeability of 440.2±3.3 Barrer and a CO 2 /CH 4 separation factor of 28±0.6. This study indicates that introducing the amphiphilic polymer into the blend membranes is an efficient strategy for gas separation.